The Whole Atmosphere Community Climate Model Version 6 (WACCM6). Issue 23 (2nd December 2019) - Gettelman, A.; Mills, M. J.; Kinnison, D. E.; Garcia, R. R.; Smith, A. K.; Marsh, D. R.; Tilmes, S.; Vitt, F.; Bardeen, C. G.; McInerny, J.; Liu, H.‐L.; Solomon, S. C.; et al.
Abstract: The Whole Atmosphere Community Climate Model version 6 (WACCM6) is a major update of the whole atmosphere modeling capability in the Community Earth System Model (CESM), featuring enhanced physical, chemical and aerosol parameterizations. This work describes WACCM6 and some of the important features of the model. WACCM6 can reproduce many modes of variability and trends in the middle atmosphere, including the quasi‐biennial oscillation, stratospheric sudden warmings, and the evolution of Southern Hemisphere springtime ozone depletion over the twentieth century. WACCM6 can also reproduce the climate and temperature trends of the 20th century throughout the atmospheric column. The representation of the climate has improved in WACCM6, relative to WACCM4. In addition, there are improvements in high‐latitude climate variability at the surface and sea ice extent in WACCM6 over the lower top version of the model (CAM6) that comes from the extended vertical domain and expanded aerosol chemistry in WACCM6, highlighting the importance of the stratosphere and tropospheric chemistry for high‐latitude climate variability. Plain Language Summary: This manuscript describes the Whole Atmosphere Community Climate Model Version 6 (WACCM6), a chemistry and climate model which extends up to 140 km in the upper atmosphere. WACCM6 reproduces many important features of the climate system, and the addition of detailed chemistry and the higher than normal model top produces slightly improved simulations of the Arctic region. Key Points: WACCM6 is a major upgrade to previous versions WACCM6 can reproduce many modes of variability and trends in the middle atmosphere WACCM6 provides improvements in high‐latitude climate variability at the surface and sea ice extent over a low top model